2020
DOI: 10.1021/acs.joc.0c01537
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3-Dihydro-4-pyridones and 4-Pyridones by the Cyclization Reaction of Ester-Tethered Enaminones

Abstract: 2,3-Dihydro-4-pyridone skeleton is an important building block in organic synthesis because it features several reaction sites with nucleophilic or electrophilic properties. Herein, we disclose a method for its formation by intramolecular cyclization of ester-tethered enaminones, which can easily be synthesized from readily available materials, such as amines, activated alkynes, and activated alkenes. 2,3-Dihydro-4-pyridones have been isolated in 41−90% yields. We also demonstrate the transformation of these h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…The chemistry of these heterocycles is actively developed not only for the design of biologically important compounds [ 7 , 8 , 9 ], but also for effective preparation in the industry [ 1 , 2 , 3 , 10 , 11 , 12 , 13 , 14 , 15 ]. At the same time, there is a need to search for new multifarious pyridone building blocks [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and convenient synthetic tools for the construction of polycyclic pyridones [ 1 , 2 , 3 , 15 ], including CH functionalization [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of these heterocycles is actively developed not only for the design of biologically important compounds [ 7 , 8 , 9 ], but also for effective preparation in the industry [ 1 , 2 , 3 , 10 , 11 , 12 , 13 , 14 , 15 ]. At the same time, there is a need to search for new multifarious pyridone building blocks [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and convenient synthetic tools for the construction of polycyclic pyridones [ 1 , 2 , 3 , 15 ], including CH functionalization [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our project directed towards the synthesis and utilization of (di)enaminones as synthetic intermediates, 18 we observed that the solvent-free and metal-free silica gel-catalyzed synthesis of useful intermediates, polyfunctionalized dienes 1 , 15,19 yielded DHPs 2 as by-products which were isolated as a mixture of regioisomers (Scheme 1). 18 a Although the synthesis of 1,4-DHPs from an amine and ethyl propiolate under (Lewis) acid catalysis 20 and organocatalytic conditions 21 was reported, we are not aware of any example of the formation of the 1,2-isomer from the mentioned starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Existing MCP can achieve a wide source of low-cost raw materials in its production, but the environmental pollution caused by the use of toxic and hazardous substances in the production process still remains a difficult problem. In addition, pyridones are also a class of organic compounds with important biological activity and medicinal value (Stojanovic et al 2020;Houshmandyar et al 2021). Cyclic pyridones constitute a promising family of antimalarial compounds that have been shown to maintain excellent in vitro activity and in vivo efficacy in the Plasmodium jovis model and the humanized mouse model of Plasmodium falciparum (Felipe 2018).…”
Section: Introductionmentioning
confidence: 99%